'Because life it selfe is but motion': Toward an anthropology of mobility. (December 2015) - Lelièvre, Michelle A; Marshall, Maureen E
Over the last two decades, mobility has gained new prominence within anthropology, particularly in theories of globalization, immigration, and subjectivity. At stake in all of the recent ethnographic and archaeological work on mobility is not just how anthropologists conceptualize mobility, but also how we conceptualize the political. Many discussions of mobile subjects have seemed to challenge traditional understandings of the political that are synonymous with a monolithic state and a stable, sedentary subject population. Yet, we maintain that there are still challenges to a coherent anthropological theory of mobility and its relation to the political. To address these challenges, we forward a conceptual framework of mobility that is grounded in the practices, perceptions, and conceptions of movement entwined with processes of emplacement. Illustrated by case studies from the Late Bronze Age (1500 – 1150 B.C.) South Caucasus and nineteenth-century Nova Scotia, the conceptual framework that we detail understands mobility as a mediator between political subjects and political institutions, thus making it possible to examine how subjects and institutions are continuously remade in relation to each other.